Análise de livros didáticos e dimensões da ciência na formação inicial de professores de física - Schirmer, Saul Benhur (2016)
The wide distribution of books to public schools of basic education under the National Textbook Program (PNLD) kept the Textbook (LD) as an important topic in research related to education over the past decades. In this program, it is up for the teachers to choose the textbooks which will be used in schools. However, many studies of the area have pointed out problems in the process and highlighting the need to discuss it in teacher education. Thus, the present study aims to investigate how to support future Physics teachers to carry out the analysis and choice of LD. In order to achieve this goal, journals and conferences concerning teaching were surveyed to investigate the possible contributions that these publications could present. Results show that research focuses on the analysis of conceptual aspects of textbooks and that there are virtually no records of propositional actions or discussions that can directly contribute to teacher training. In this context, the present investigation focused on designing, implementing and evaluating a didactic proposal that considers different dimensions associated with science as a starting point for evaluating textbooks. The proposal was implemented within the students of the Physics subproject of the Institutional Introduction to Teaching Scholarship Program (PIBID) of Federal University of Santa Maria. Taking the historical and philosophical, empirical and technological dimensions into account, it was proposed to the students an analysis of the contents of Optics in the textbooks approved by PNLD in 2015. To execute this, scripts were formulated from teaching research results. Data collection was performed by means of the participants' written records, which for each analyzed dimension were constituted by reports of their analysis, their conclusions and a daily activities diary. Results showed that participants had significant advances both in relation to the review process, by overcoming mere verification and starting to argue about the analyzed aspects, and also in relation to the dimensions addressed as changes in strictly cumulative view of science, recognizing the need for experimental activities in a more open character and that technology has limited role in the collections. Furthermore, textbook analysis by the dimensions of science and its pedagogical aspects proved to be a way to articulate and promote further reflection. Thus, this approach showed itself to be a fruitful way to train more qualified teachers for the professional task of analysis and choice of textbooks.